Pengaruh teknik relaksasi aroma terapi lavender dan autogenik terhadap penurunan kecemasan pada pasien pra operasi Sectio Caesarea - Sri Nurhayati; Senja Atika Sari (Holistik Jurnal Kesehatan, 2022)
Background: Sectio Caesarea (SC) is a surgery to give birth a fetus through an incision in the abdominal wall and uterus so that the fetus can be born intact and healthy. In undergoing the process of preparing for a Sectio Caesarea, the patient will be faced with the image of the surgical process, the anaesthesia process, the safety of the baby, her safety, pain and various other problems that make the patient experience discomfort or which usually becomes an anxiety. Anxiety is an emotion and subjective experience of a person that makes him uncomfortable.Purpose: To determine the effect of lavender aromatherapy and autogenic relaxation techniques on reducing anxiety in preoperative Sectio CaesareaMethod: A quantitative research with a cross sectional approach using a statistical test independent T test. The research was conducted in the operating ward at Puri Adya Paramita Hospital. The population was 80 mothers who gave birth while, The sampling technique in this study uses purposive sampling and obtained as research subjects was 66 mothers who underwent Sectio Caesarea.Results: Finding the difference in maternal anxiety when Sectio Caesarea was carried out in the intervention group and the control group obtained statistical test results with p value 0.001 < 0.05, means that there is a significant difference in the level of maternal anxiety when Sectio Caesarea is performed control group and intervention group by giving lavender aromatherapy and autogenic.Conclusion: There is an effect of lavender aromatherapy and autogenic relaxation techniques on reducing anxiety in preoperative Sectio CaesareaKeywords: Aromatherapy; Autogenic; Anxiety; Sectio Caesarea.Pendahuluan: Sectio Caesarea (SC) adalah suatu pembedahan guna melahirkan janin lewat insisi pada dinding abdomen dan uterus sehingga janin dapat lahir secara utuh dan sehat. Dalam menjalani proses persiapan operasi sectio caesarea, pasien akan dihadapkan dengan bayangan mengenai proses operasi, proses pembiusan, keselamatan bayi, keselamatan dirinya, kesakitan dan berbagai masalah lainnya yang membuat pasien akan mengalami ketidaknyamanan atau yang biasanya menjadi sebuah kecemasan, kecemasan adalah sebuah emosi dan pengalaman subjektif dari seseorang yang membuat tidak nyaman.Tujuan: Mengetahui pengaruh teknik relaksasi aroma terapi lavender dan autogenik terhadap penurunan kecemasan pada pasien pra operasi Sectio CaesareaMetode: Penelitian kuantitatif dengan pendekatan cross sectional menggunakan uji statistik uji T independent. Penelitian dilakukan di unit ruang operasi RSIA Puri Adya Paramita. Populasi sebanyak 80 orang ibu bersalin. Teknik pengambilan sampel dalam penelitian ini menggunakan purposive sampling dan sampelnya sebanyak 66 orang ibu yang menjalani SC.Hasil: Perbedaan kecemasan ibu saat dilakukan Tindakan Sectio caesarea kelompok intervensi dan kelompok kontrol diperoleh hasil uji statistic nilai p value 0,001 < α 0,05 yang artinya ada perbedaan yang bermakna terhadap tingkat kecemasan ibu saat dilakukan Tindakan section caesarea pada kelompok kontrol dan kelompok intervensi dengan memberikan aroma therapy lavender dan autogenik.Simpulan: Terdapat pengaruh teknik relaksasi aroma terapi lavender dan autogenik terhadap penurunan kecemasan pada pasien pra operasi Sectio Caesarea